EKSPLORASI DAN INDENTIFIKASI JENIS-JENIS ANGGREK DI KAWASAN HUTAN PULAU MANSINAM KABUPATEN MANOKWARI - NIKSON REZALL BIETH; AGUSTINA Y.S. AROBAYA (Fakultas Kehutanan UNIPA, 2020)
This study was focusing on identifying types of epiphytic orchid species through field survey by establishing plots and tracks for observation. The main parameter in the study was morphological characteristic of epiphytic orchid that covers shape, root, stem, leaf, fruit, and flower as well as its growing habitat. From the result standpoint, 6 epiphytic orchid species were identified that consisted of Dendrobium bifalce Lindl, Dendrobium mirbelianum Gaudich, Dendrobium schulleri J.J.Sm, Grammatophylum scriptum (Lindl.) Blume, Grammatophylum speciosum Blume, and Pomatocalpa sp aff Marsupial. In addition to their hosted plant, the result found several species of plant such as Mangifera indica, Alstonia scholaris, Baringtonia asicatica, Pometia sp, and Terminalia catappa which their growth was mostly sticking to the main stem and branch.